DAMPAK E-COMMERCE ATAS PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA MAKASSAR SELATAN - Hadriana Hanafie (AkMen JURNAL ILMIAH, 2016)
This study aims: to study and analyze the impact of e-commerce on tax revenue in the Tax Office (KPP) Pratama South Makassar. This study used a qualitative descriptive analysis method. The research data used were obtained from the Tax Office (KPP) Pratama South Makassar. The results of this study show that: the impact of e-commerce on tax revenue in the Tax Office (KPP) Pratama South Makassar rated good because tax revenue has increased every year. This is due to the compliance and awareness of taxpayers (WP) as the perpetrators of e-commerce transactions to pay his taxes every year, this may happen because the payment of taxes through e-commerce systems can be easily, quickly, saving time and costs, and to do each time, so the potential tax revenue can be collected optimally by upholding the principle of social justice and provide excellent service to taxpayers (WP), it creates a transparency that can minimize any fraud, leakage and fraud (KKN) in tax revenue in the tax Office (KPP) Pratama South Makassar.